In Vitro Evaluation of Phytoextract Against Alternaria Solani Caused Early Blight of Tomato (Journal of Plant Disease Sciences, 2023)
Tomato is a fruit vegetable that ranks second to potato in terms of global acreage and top among processing crops. Tomato production is normally hampered by a variety of diseases, the most serious of which being early blight caused by Alternaria solani. Recently, there has been an increase in concern about the impact of synthetic fungicides on environmental and food safety, necessitating the exploration of various alternatives that are favorable to the user, consumer, and the general environment. The purpose of this study was to see how effective phyto-extracts were against A. solani. In vitro evaluation of various phyto-extracts at 10% and 20% concentrations revealed that Azadirecta indica inhibited mycelial growth of the test pathogen with 73.03% and 75.36% respectively, whereas Parthenium hysterophorus inhibited mycelial growth with 73.03% and 61.96% respectively, which was found to be comparativelylesseffective when comparedto theuntreated control.
Keywords: Tomato; Alternaria solani; Evaluation; Phyto-extract